2018
DOI: 10.1002/bit.26850
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast–endothelium signaling involves angiogenesis and apoptosis in a dynamic bioprinted placenta model

Abstract: Trophoblast invasion and remodeling of the maternal spiral arteries are required for pregnancy success. Aberrant endothelium-trophoblast crosstalk may lead to preeclampsia, a pregnancy complication that has serious effects on both the mother and the baby. However, our understanding of the mechanisms involved in this pathology remains elementary because current in vitro models cannot describe trophoblast-endothelium interactions under dynamic culture. In this work, we developed a dynamic 3D placenta model by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…By using a threedimensional bioprinted placenta model, Kuo et al performed impressive trophoblast-endothelium interaction studies. They reported that the co-culture of trophoblasts with endothelial cells significantly reduced the outgrowth and network formation of endothelial cells and induced endothelial cell apoptosis, shown by a significant upregulation of apoptosis marker (35). Trophoblast invasion is temporally and spatially regulated by autocrine (trophoblastic) and paracrine (uterine) factors as well as cell-to-cell and cell-to-matrix interactions (36).…”
Section: Interaction Of Stromal Cells Immune Cells and Trophoblastsmentioning
confidence: 99%
“…By using a threedimensional bioprinted placenta model, Kuo et al performed impressive trophoblast-endothelium interaction studies. They reported that the co-culture of trophoblasts with endothelial cells significantly reduced the outgrowth and network formation of endothelial cells and induced endothelial cell apoptosis, shown by a significant upregulation of apoptosis marker (35). Trophoblast invasion is temporally and spatially regulated by autocrine (trophoblastic) and paracrine (uterine) factors as well as cell-to-cell and cell-to-matrix interactions (36).…”
Section: Interaction Of Stromal Cells Immune Cells and Trophoblastsmentioning
confidence: 99%
“…This is characterized by elevated blood pressure and also a noteworthy quantity of protein present in the urine of pregnant women due to reduced trophoblast invasion of maternal spiral arteries. Nevertheless, there are few biomodels able to reproduce this pathology [ 23 , 55 , 57 ]. A promising model was proposed by Kuo and co-workers [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, trophoblast inflammatory response was up-regulated after 24 h but not before; it is postulated that, once the epithelium is breached, inflammation could act as a regulatory mechanism to prevent excessive invasion. Interestingly, angiogenesis was continuously increased along the 24 h of co-culture; if extrapolated to the in-vivo situation, the transcriptional up-regulation during this early time could trigger signalling required for remodelling of the maternal vasculature needed for placental development (Kuo et al, 2019;Zhou et al, 2003). Regulation of the unfolded protein response, which is linked to endoplasmic reticulum stress, has been related to placental development (Burton and Yung, 2011;Yung et al, 2014).…”
Section: Discussionmentioning
confidence: 99%